Regulatory challenges in the production and commercialization of organic wheat in Brazil (Research, Society and Development, 2025)
The preservation of wheat and the storage of any bulk grain, when carried out properly, can easily last from six to eight years or more without losing any of its nutritional benefits. The aim of this research was to address, through a documentary analysis of primary sources in regulations, combined with a literature review, the organic products system, specifically wheat grains, and the challenges related to managing this segment in Brazil, based on current legislation. The consulted literature indicates that the use of a modified atmosphere with carbon dioxide or the application of diatomaceous earth is permitted for treating organic wheat, according to Normative Instruction No. 46 of October 6, 2011, from MAPA. Another method gaining prominence in organic wheat preservation is the VacQPack technique, which offers bio-fumigation based on storage temperature and vacuum (low pressure). Among the presented methods for organic product treatment, the most recommended, cost-effective, and suitable for large volumes was the modified atmosphere technique, which is already available in the Brazilian market. The vacuum system technique could not be compared due to the lack of cost references in literature and because it is a relatively new process. Therefore, organic wheat, like other grains and seeds, still requires more research post-harvest to develop efficient and competitive preservation methods.